2020
DOI: 10.1002/hep.30896
|View full text |Cite
|
Sign up to set email alerts
|

Immune Exhaustion of T Cells in Alveolar Echinococcosis Patients and Its Reversal by Blocking Checkpoint Receptor TIGIT in a Murine Model

Abstract: Background and Aims The cestode Echinococcus multilocularis infection, a serious health problem worldwide, causes alveolar echinococcosis (AE), a tumor‐like disease predominantly located in the liver and able to spread to any organs. Until now, there have been few studies that explore how T‐cell exhaustion contributes to the parasite’s escape from immune attack and how it might be reversed. Approach and Results In this study, we found that liver T‐cell immunoreceptor with immunoglobulin and immunoreceptor tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 44 publications
(131 reference statements)
4
67
0
1
Order By: Relevance
“…Over the past decades, studies performed in mice models and in patients demonstrated that the persistence of the larval E. multilocularis infection led to immune tolerance, which is mediated by T‐cell exhaustion 18 . Arguments concur to support a mechanistic hypothesis that several inhibitory immune checkpoints involved in lymphocytic proliferation are upregulated during alveolar echinococcosis: the previous publications demonstrating the role of the PD‐1/PD‐L1 pathway, 9,10 recent Chinese studies showing increased expression of LAG‐3 and of TIGIT in T cells of mice infected with E. multilocularis 19,20 as well as the present in vitro results.…”
Section: Discussionmentioning
confidence: 95%
“…Over the past decades, studies performed in mice models and in patients demonstrated that the persistence of the larval E. multilocularis infection led to immune tolerance, which is mediated by T‐cell exhaustion 18 . Arguments concur to support a mechanistic hypothesis that several inhibitory immune checkpoints involved in lymphocytic proliferation are upregulated during alveolar echinococcosis: the previous publications demonstrating the role of the PD‐1/PD‐L1 pathway, 9,10 recent Chinese studies showing increased expression of LAG‐3 and of TIGIT in T cells of mice infected with E. multilocularis 19,20 as well as the present in vitro results.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, sample acquisition from LME liver and adjacent liver tissues (respectively for experimental and control groups) has been introduced to study immunology, brosis, pathophysiological changes etc. of the host [5][6][7][8]. However, there was no clear evidence for such sampling method that could clearly differentiate the real experimental and control liver tissues by separating the immune cell in ltrative boundary.…”
Section: Introductionmentioning
confidence: 99%
“…In this prospective study, we collected surgical hepatic AE subjects' preoperative computed tomography (CT), PET/CT, clinical data, and LME liver samples acquired through multi-site sampling method (MSS). Our primary research results concerning such sampling method for immunological study has been reported as "at least 2 cm distant from lesion" as a method to obtain adjacent normal liver tissue for controls previously [5]. Currently, we nished this prospective study that mainly focused on TBRs' differences and quanti cation of LME ranges in several lesion categories.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, sample acquisition from LME liver and adjacent liver tissues (respectively for experimental and control groups) has been introduced to study immunology, fibrosis, pathophysiological changes etc. of the host [5][6][7][8]. However, there was no clear evidence for such sampling method that could clearly differentiate the real experimental and control liver tissues by separating the immune cell infiltrative boundary.…”
Section: Introductionmentioning
confidence: 99%
“…In this prospective study, we collected surgical hepatic AE subjects' preoperative computed tomography (CT), PET/CT, clinical data, and LME liver samples acquired through multi-site sampling method (MSS). Our primary research results concerning such sampling method for immunological study has been reported as "at least 2 cm distant from lesion" as a method to obtain adjacent normal liver tissue for controls previously [5]. Currently, we finished this prospective study that mainly focused on TBRs' differences and quantification of LME ranges in several lesion categories.…”
Section: Introductionmentioning
confidence: 99%